Experimental investigation on room-temperature flexible composite phase change materials in thermal management of power battery pack. (August 2022) - Yang, Xiaoping; Zhang, Zhihao; Cai, Zhuodi; Chen, Yanfeng
Highlights: A flexible phase change material with good room-temperature flexibility is proposed. The material can maintain soft and low rigidity in the range of −40 °C to 60 °C. The experimental platform of phase change material cooling system is constructed. The maximum temperature is controlled below 45.5 °C at the discharge rate of 2.5C. Abstract: Using composite phase change materials (CPCM) for battery thermal management system (BTMS) has various advantages, such as high latent heat, simple structure, no energy consumption. The great rigidity and poor elasticity of thermally induced flexible CPCM at room temperature are still a major problem, and they may lead to low installation convenience and high contact thermal resistance. In this study, a novel flexible CPCM with good room-temperature flexibility is proposed, which is synthesized with thermoplastic elastomer and polyolefin elastomer as support material, paraffin as phase change material, and silicon carbide as heat conduction enhancer. The micromorphology, crystal structure, and mechanical properties of the materials are characterized and analyzed. The material can maintain soft and low rigidity in the range of −40 °C to 60 °C and has good chemical, physical properties and thermal stability. A CPCM-based cooling system for square power battery module is designed. Six charge–discharge cycles are conducted under different discharge rates to explore the cooling performance of BTMS. The results revealed that under the extreme ambient temperature of 40 °C and after 6 cycles of high discharge rate at 2.5C, the maximum temperature and average temperature difference of the battery module are 56 °C and 3.9 °C, which are lower than that of the battery module cooled by the wind speed of 5 m/s. With these outstanding performances, the battery module with designed room-temperature flexible CPCM can provide insights into the passive thermal management and other energy storage fields.